A Strong Correlation Between Relativistic Electron Microbursts and Patchy Aurora. Issue 18 (12th September 2021) - Shumko, M.; Gallardo‐Lacourt, B.; Halford, A. J.; Liang, J.; Blum, L. W.; Donovan, E.; Murphy, K. R.; Spanswick, E.
Abstract: In this letter, we present the results of a conjunction between the Solar Anomalous and Magnetospheric Particle Explorer (SAMPEX) satellite and a Time History of Events and Macroscale Interactions during Substorms (THEMIS) all‐sky imager in Gillam, Canada, showing a high correlation between relativistic, > 1  MeV, electron microbursts and a type of pulsating aurora called patchy aurora. The correlation was 0.8, and is not serendipitous. While the relationship between pulsating aurora and 10–100s keV microbursts has been previously predicted, here we show a strong association between keV and MeV electron dynamics, possibly spanning two orders of magnitude. Importantly, this result shows that the dynamics of relativistic radiation belt electrons are at times intimately tied to keV electron precipitation, and cannot be studied in isolation. Plain Language Summary: In this letter, we present a coordinated observation between a low Earth orbiting satellite, orbiting at 400 km altitude above Earth's surface, and an auroral all‐sky imager in Canada. This observation showed a connection of a type of pulsating aurora, called patchy aurora, with extremely energetic and intense bursts of electron radiation called microbursts. This link is surprising because the electron energies responsible for auroral light are 100 times lower than the electrons that were directly observed in space. Our result implies that the mechanism responsible for patchy aurora and microbursts is likely the same, and could be capable of affecting electrons with vastly different energies. This result is a major step toward unifying the microburst and patchy aurora phenomena and shows that the dynamics of high‐energy electrons located in near‐Earth space can be intimately tied to much lower energy electron precipitation, and must therefore be studied together. Key Points: We identified a conjunction between the low Earth orbiting Solar Anomalous and Magnetospheric Particle Explorer (SAMPEX) satellite and a Time History of Events and Macroscale Interactions during Substorms (THEMIS) all‐sky imager at Gillam, Canada We found a high correlation between patchy aurora and >1 MeV electron microburst precipitation observed during the conjunction This correlation suggests a close connection between relativistic electron microbursts and patchy aurora